Vytvoření modelu kompetencí krizového manažera malého podniku za použití Saatyho metody - Mikušová, Marie; Čopíková, Andrea (Univerzita Pardubice, 2015)
The article presents a model of crisis manager competencies. It was created in cooperation with the owners of small businesses. Based on brainwriting the competencies required for a crisis manager were generated. Decision-making method AHP was used for competencies decomposition into two levels. On the first level three groups were placed. The are called managerial competence, interpersonal and technical. At the second level, these groups were further decomposed, e.g. on competencies like leadership, strategic thinking, time management, financial management, resilience, independence in solving problems, team work etc. The respondents performed quantitative pairwise comparisons by Saaty's method. Respondents evaluated competencies at both levels. After evaluating Saaty's matrices modified on the basis of comprehensive results of all respondents the competency model of crisis manager was created. The authors do not claim the permanence of presented model and also accept the possibility of derogation of the competencies required for the function of a crisis manager for large enterprises.
Creating of a competence model of small enterprise crisis manager using Saaty’s method
Keywords: AHP; brainwriting; competency model; crisis manager; Saaty’s method; small enterprise; M12; C10